2011
DOI: 10.1093/eurheartj/ehq491
|View full text |Cite
|
Sign up to set email alerts
|

Minor elevations in troponin I are associated with mortality and adverse cardiac events in patients with atrial fibrillation

Abstract: Minor elevations in troponin I on hospital admission are associated with mortality and cardiac events in patients with atrial fibrillation and might be useful for risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 26 publications
1
65
1
1
Order By: Relevance
“…Recently, cardiac troponins have been known to be associated with incident AF in the general population,26 and are associated with delayed diagnosis of AF after stroke 27. However, it is still unclear whether the pathomechanism of troponin elevation in AF is due to AF itself (eg, accompanying tachycardia with a fast ventricular response) or due to pre‐existing heart failure with or without LAE 28. Thus, our results could suggest that structural heart problems may play an important role in the identification of newly detected AF in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cardiac troponins have been known to be associated with incident AF in the general population,26 and are associated with delayed diagnosis of AF after stroke 27. However, it is still unclear whether the pathomechanism of troponin elevation in AF is due to AF itself (eg, accompanying tachycardia with a fast ventricular response) or due to pre‐existing heart failure with or without LAE 28. Thus, our results could suggest that structural heart problems may play an important role in the identification of newly detected AF in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative 3-year survival rates were 78% in the non-detectable troponin I group, 62% in the minor elevation group, and 57% in the positive troponin I group (log-rank P < 0.001). [23] A sub-study of the Randomized Evaluation of Long-Term Anticoagulant Therapy trial (RE-LY), performed in 6189 patients with AF and treated with either warfarin or dabigatran, found that cTnI was predictive of thromboembolic events and cardiovascular mortality, and even after adjustment by potential confounding factors, the risk of stroke or systemic embolism was doubled to fivefold higher for cardiovascular mortality, in patients with the highest quartiles. Hijazi et al demonstrated that persistent elevation of troponin I was seen in nearly half of the patients in the RE-LY study cohort comprising of patients with anticoagulated AF with ≥1 risk factor for stroke.…”
Section: Prognostic Value Of Elevated Troponin Levelsmentioning
confidence: 99%
“…Some investigators believe that increased wall stress, demand-supply mismatch, or angiotensin 2-induced oxidative stress are possible explanations for troponin elevations in selected AF patients. 46 …”
Section: Troponinmentioning
confidence: 99%
“…Because these studies used different assays, an absolute number for troponin elevation cannot be established to guide clinical decision making, such as that available for myocardial infarction. [45][46][47][48] In another study, patients with elevated levels of hstroponin T were 2.2 times more likely to have adverse cardiovascular events and were at 1.8-fold increased risk for all-cause mortality compared with patients with normal hs-TnT, even after adjusting for CHADS 2 score. 49 These results were derived from real-world AF patients who are receiving chronic (.6 months) stable anticoagulation with warfarin (time in therapeutic range, .70%) and are complementary to the previously discussed results of the RE-LY and ARISTOTLE clinical trials.…”
Section: Singla Et Almentioning
confidence: 99%